Escapism as Reflected in Tennessee William’s The Glass Menagerie - ' Nensia (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
Escapism is a part of psychology which in this research connected into literature as an interdisciplinary study which shows inclination of human personality to seeking for a way out or escape from unpleasant realities. The aim of the research was to describe the characters got acquainted with escapism and the way the characters’ cope with escapism in their daily life. The research employed a descriptive qualitative method with psychoanalytical approach of Sigmund Freud’s personality structure from anxiety theory, defense and problem solving mechanism. Data sources were primary and supporting data. The primary data were taken from Tennessee William’s The Glass Menagerie, and supporting data were taken from the books, journals, articles, and internet sources. The research indicated that each character experienced anxiety that made them got acquainted with escapism. They had their own way in dealing with escapism through defense and problem solving mechanism. Some characters solved emotional problems with negative mechanism consciously or unconsciously, and others handled emotion with positive mechanism, therefore the result were also positive.